Rice production responses in Cambodia - Yu, Bingxin; Fan, Shenggen (International Food Policy Research Institute, 2009)
This paper analyzes how Cambodian farmers and the Cambodian government can respond to increasing rice prices. The study estimates rice production responses in Cambodia using the Cambodian Socio-Economic Surveys (CSES) conducted in 2004 and 2007. The results indicate that there is huge potential for output expansion in the Cambodian rice sector, and that farmers can respond to high prices by increasing their use of inputs such as fertilizers and irrigation. Our findings also suggest that the Cambodian government needs to design an investment strategy that relaxes constraints in rural infrastructure (e.g., transportation and electricity) in order to increase agricultural production and productivity and boost farmers’ incomes.